Atomic absorption spectroscopy for determination of some mineral contents in selected fruits consumed by BSAC students / Norazlan Mohmad Misnan - Mohmad Misnan, Norazlan (Faculty of Applied Sciences, 2009)
Atomic Absorption spectroscopy (AAS) was used to determine calcium, copper, magnesium, sodium, iron and zinc in six fruits namely papaya, pineapple, mango, banana, honeydew and flesh of coconut. Samples were wet ashing using nitric acid and hydrogen peroxide and calibration was accomplished using absorption against concentration of working standard solution. Data obtained are reported in mg/g and are compared with US DA data. Fruits are identified which may be considered good sources of selected elements and differences in elemental content for multiple verities of fruits is studied. Survey on BSAC students was done and shows that for six fruits in this study mango was a fruits that BSAC student mostly like and the least was coconut. However from the analysis on six types of fruits, coconut shows that it contains greatest amount of minerals compared to other five fruits.